The Security Sector and Poverty Reduction Strategies - Carrington, Tim; Post, David (World Bank, Washington, DC, 2012)
In conflict-affected countries, insecurity can worsen the incidence of poverty, undercut the delivery of basic services, and leave segments of the population chronically vulnerable. Because security provision is both a core function of the state, and a necessary condition for the delivery of other essential services, it should be an integral part of any strategy for recovery and development. Poverty Reduction Strategies - the standard tool for organizing medium-term economic and social policies for growth and poverty reduction can be more effective if they adopt a strategic approach to serious security challenges. This note is based on the security sector and poverty reduction strategies, an issue note prepared as part of an analytical and technical assistance program conducted by the social development department in cooperation with colleagues across the Bank and Department for International Development (DFID)-UK. The issue note discusses entry points for engagement in the security sector in countries where insecurity is a major contributor to poverty and vulnerability. It also explores the best ways of integrating security reforms into a poverty agenda, and the role the World Bank might play as an international partner.